OPTIMALISASI PENGIRIMAN DATA DEPARTURE DAN ARRIVAL MESSAGE PESAWAT MILITER OLEH UNIT ATS DI BANDAR UDARA INTERNATIONAL SUPADIO PONTIANAK - Muhammad Erdiansyah Ceisar Ramadhan; Dewi Ratnasari; Siska Wijayanti (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
ATS Message distribution is one of the things that must be done by the ATS unit. Therefore the distribution of ATS Messages must be properly to reduce dataerrors in the aircraft in operation. The purpose of this research is to optimize the delivery of departure and arrival message data of military aircraft at Pontianak Supadio Airport so that the distribution of ATS messages can be optimized. This final task uses a qualitative descriptive research design that uses 2 variables: Military aircraft flight (Variable X) and Optimization of news delivery Departure and Arrival of military aircraft at pontianak supadio airport (Variable Y). Data collection techniques using observations, interviews, case studies and literature studies. The interview was conducted by 3 Aeronautical Communication Officer personnel at Pontianak Supadio Airport. From the results of the research that has been done by the authors the expected conclusion is the distribution of ATS messages should be optimized. The problem solving provided by the author is to use Microsoft excel to record what military aircraft data will fly tomorrow manually.